Globalization with development (1999)
Summarizes the main characteristics of the current international environment affecting the formulation of economic policies by the region's countries. Lists the main elements which from the Secretariat's point of view, could make up the region's development agenda. Outlines the economic issues upon which the attention of the governments of Latin America and the Caribbean is focused today. Delineates probable trends of the next few years. Contains some general thoughts about the idées-forces which, in the opinion of the Ssecretariat, should drive UNCTAD's action in coming years, as well as reflections on the development strategies of Latin America and the Caribbean.
Keywords: ECONOMIC DEVELOPMENT